MODEL PEMBELAJARAN WEB COURSE DAN WEB CENTRIC COURSE TERHADAP PRESTASI BELAJAR - Ima Sugioto Putri; Sulton Djasmi; Helmi Fitriawan (Indonesia Journal of Educational Technology, 2017)
This study aimed to analyze: 1) the interaction between the learning model of WC and the WCC with the ability early on student achievement in the subject of SBD, 2) differences in the achievement of students in the subject of SBD using model WC and WCC, 3) differences in student achievement in the course of SBD with lower initial ability to use learning models WC and WC, and 4) differences in learning achievement SBD subjects with high baseline capabilities using model WC and WCC. The study was conducted in Bandar Lampung technocrat College majoring in Information Systems. Cluster sampling technique Random Sampling. Data were analyzed using essay test with normality and homogeneity test. The conclusions of this study were 1) There is no interaction between learning models WC and WCC (sig 0.017 <0.05), initial capability (sig 0.00 <0.05) and the interaction model and the ability of early (sig 0.002 <0.05) , 2) achievement using a model of WC higher compared with the WCC learning model (sig 0.00 <0.05), 3) the learning achievement with lower initial ability to use learning models WCC higher than the learning model WC (sig 0.55> 0 , 05), and 4) the learning achievement with high initial capabilities using model WCC higher than the learning model WC (sig 0.000 <0.05).Penelitian ini bertujuan untuk menganalisis: 1) interaksi antara pembelajaran modelWCdanWCCdengan kemampuan awal terhadap prestasi belajar mahasiswa pada mata kuliah SBD, 2) perbedaan prestasi belajar mahasiswa pada mata kuliah SBD menggunakan model pembelajaranWCdanWCC, 3) perbedaan prestasi belajar mahasiswa pada mata kuliah SBD dengan kemampuan awal rendah menggunakan model pembelajaranWCdanWC,dan 4) perbedaan prestasi belajar mata kuliah SBD dengan kemampuan awal tinggi menggunakan model pembelajaranWCdanWCC.Penelitian dilakukan di Perguruan Tinggi Teknokrat Bandar Lampung pada jurusan Sistem Informasi. Teknik pengambilan sampel denganCluster Random Sampling. Teknik analisis data menggunakan tesessaydengan uji normalitas dan homogenitas. Simpulan dari penelitian ini adalah 1) terdapat interaksi antara pembelajaran modelWCdanWCC(sig 0,017<0,05), kemampuan awal (sig 0,00<0,05) serta interaksi model dan kemampuan awal (sig 0,002<0,05), 2) prestasi menggunakan model WC lebih tinggi dibandingan dengan model pembelajaran WCC (sig 0,00<0,05), 3) prestasi belajar dengan kemampuan awal rendah menggunakan model pembelajaranWCClebih tinggi dibandingkanmodel pembelajaranWC(sig 0,55>0,05), dan 4) prestasi belajar dengan kemampuan awal tinggi menggunakan model pembelajaranWCClebih tinggi dibandingkanmodel pembelajaranWC(sig 0,000<0,05).Kata kunci:sistem basis data,web course, web centric course.